Money, Banking, and the Economy / Sixth Edition - Aliber Robert Z.; Duesenberry James S; Mayer Thomas (W.W. Norton & Company, 1995)
Preface, Finance - Institutions and Theory, Money, Stocks and Bonds and Financial Institutions, Financial Principles, Asset Markets, Interest Rates, The Depository Institutions Industry, Inside the Depository Institution, International Banking, The Failure of the Deposit-Insurance System, Financial Policy: Some Remaining Issues, Central Banking, The Supply of Money, The Measurement of Money, The Creation of Money, Bank Reserves and Related Measures, Money and National Income and the Price, The Determinants of Aggregate Expenditures, Aggregate Expenditures and the Interest Rate, Aggregate Expenditures and the Demand for Money, Aggregate Expenditures: The Complet Model, Inflation and Unemployment, The Quantity Theory and Monetarism and the Credit View, Monetary Policy, Targets and Instruments, The Impact of Monetary Policy, Alternative Monetary Standards, The International Monetary System, Future Directions for the International Monetary System, Glossary, Index.